2011
DOI: 10.1104/pp.111.191452
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Chromatin-Remodeling Proteins in the Repair of Ultraviolet-B-Damaged DNA      

Abstract: The genome of plants is organized into chromatin, affecting the rates of transcription, DNA recombination, and repair. In this work, we have investigated the consequences of reduced expression of some chromatin-remodeling factors and histone acetylation in maize (Zea mays) and Arabidopsis (Arabidopsis thaliana) in their participation in DNA repair after ultraviolet (UV)-B irradiation. Plants deficient in NFC102/NFC4 or SDG102/SDG26 showed more damaged DNA than wild-type plants; however, the Arabidopsis chc1 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 69 publications
4
88
0
Order By: Relevance
“…Thus, chromatin structure regulates DNA damage signaling and histone modifications coordinate DNA repair (Sun et al, 2010). In accordance with these data, plant ham1 and ham2 mutants show increased DNA damage after UV-B irradiation (Campi et al, 2012). Therefore, the interaction between ASF1 and HAM proteins may be crucial to regulate cell cycle progression after a genotoxic stress.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, chromatin structure regulates DNA damage signaling and histone modifications coordinate DNA repair (Sun et al, 2010). In accordance with these data, plant ham1 and ham2 mutants show increased DNA damage after UV-B irradiation (Campi et al, 2012). Therefore, the interaction between ASF1 and HAM proteins may be crucial to regulate cell cycle progression after a genotoxic stress.…”
Section: Discussionsupporting
confidence: 64%
“…In plants, E2F factors contribute to the transcriptional induction of genes upon DNA damage Shen, 2002;Ramirez-Parra and Gutierrez, 2007;Lincker et al, 2008). In addition, chromatin remodeling-deficient plants show increased DNA damage by UV-B (Campi et al, 2012). Thus, it is possible that AtASF1 proteins may have a role during DNA damage and repair.…”
Section: Asf1a and Asf1b Are Regulated By E2f Transcription Factorsmentioning
confidence: 99%
“…In addition, a homozygous SALK_113834 line carrying a T-DNA insertion in the SWP73B promoter region has been used in a study to demonstrate the involvement of SWP73B in DNA repair after UV-B treatment (Campi et al, 2012). Although this mutation was reported to reduce the SWP73B transcript level by 50% compared with the wild type (Campi et al, 2012), Jégu et al (2014) found that the line has wild-type SWP73B mRNA levels and is therefore not suitable for genetic analysis. Intriguingly, although this SALK_113834 mutant is distributed as a homozygous line, we found that it is in fact heterozygous and segregates the swp73b-1 T-DNA insertion allele.…”
Section: Identification Of Swp73a and Swp73b Insertion Mutantsmentioning
confidence: 99%
“…Recently, these lines were found to show a late flowering phenotype under inductive long-day conditions (Jégu et al, 2014). In addition, a homozygous SALK_113834 line carrying a T-DNA insertion in the SWP73B promoter region has been used in a study to demonstrate the involvement of SWP73B in DNA repair after UV-B treatment (Campi et al, 2012). Although this mutation was reported to reduce the SWP73B transcript level by 50% compared with the wild type (Campi et al, 2012), Jégu et al (2014) found that the line has wild-type SWP73B mRNA levels and is therefore not suitable for genetic analysis.…”
Section: Identification Of Swp73a and Swp73b Insertion Mutantsmentioning
confidence: 99%
See 1 more Smart Citation